2009
DOI: 10.1200/jco.2008.21.3033
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Phase II Study Comparing Two Schedules of Everolimus in Patients With Recurrent/Metastatic Breast Cancer: NCIC Clinical Trials Group IND.163

Abstract: Oral everolimus has activity in metastatic breast cancer that is schedule dependent. Daily therapy with 10 mg is worthy of further study in this patient population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
183
1
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 244 publications
(193 citation statements)
references
References 23 publications
8
183
1
1
Order By: Relevance
“…This model also revealed that the lack of R-Ras2 promotes signalling compensation mechanisms in tumours similar to those seen before on the inactivation of specific PI3K/mTORC route signalling elements [39][40][41][42][43][44][45] . In those cases, such compensation effects are mostly mediated by the elimination of mTORCdependent negative feedbacks on the Raf/Erk route [39][40][41][42][43][44][45] . However, the development of these signatures in MMTVHer2 tg ;Rras2 À / À mice seems to require long-term Darwinian selection events, because primary MECs from both MMTVHer2 tg ;Rras2 À / À (this work) and Rras2 À / À knockout mice 18 do not exhibit such signatures.…”
Section: R-ras2 Deficient Tumours Develop Compensatory Mechanismsmentioning
confidence: 68%
See 1 more Smart Citation
“…This model also revealed that the lack of R-Ras2 promotes signalling compensation mechanisms in tumours similar to those seen before on the inactivation of specific PI3K/mTORC route signalling elements [39][40][41][42][43][44][45] . In those cases, such compensation effects are mostly mediated by the elimination of mTORCdependent negative feedbacks on the Raf/Erk route [39][40][41][42][43][44][45] . However, the development of these signatures in MMTVHer2 tg ;Rras2 À / À mice seems to require long-term Darwinian selection events, because primary MECs from both MMTVHer2 tg ;Rras2 À / À (this work) and Rras2 À / À knockout mice 18 do not exhibit such signatures.…”
Section: R-ras2 Deficient Tumours Develop Compensatory Mechanismsmentioning
confidence: 68%
“…Despite this, the R-Ras2-dependent PI3Ka pool is clearly relevant in vivo, given the marked tumorigenic and metastatic defects shown by R-Ras2-deficient breast cancer cells when implanted in recipient mice. The morphogenetic alterations seen in preneoplasic mammary glands of MMTV-Her2 tg ;Rras2 À / À mice, together with the signalling compensation events detected in tumours arising in those mice, are also indirect evidence in favour of defects in the PI3Ka/Akt/ mTORC route in this experimental model 30,31,[39][40][41][42][43][44][45] . However, as reconstitution experiments are not possible in this case, we cannot formally exclude the possibility that those events could be generated by defects in other R-Ras2-dependent signalling routes (Supplementary Discussion).…”
Section: R-ras2 Deficient Tumours Develop Compensatory Mechanismsmentioning
confidence: 99%
“…Recent clinical studies have shown promising antitumor activity of everolimus, an oral mTOR inhibitor, as a monotherapy and in combination therapy in breast cancer [12][13][14][15]. In patients with HER2-overexpressing advanced breast cancer, a phase I study of everolimus combined with trastuzumab and paclitaxel showed antitumor activity in patients previously considered refractory to trastuzumab [16].…”
Section: Introductionmentioning
confidence: 99%
“…Temsirolimus and everolims are currently selected for clinical trials. In the case of everolimus, on breast cancer, the Phase I trial identified the dose of 10 mg/day as optimal for further clinical development [3,11]. In the phase II, double-blind, randomized study of everolimus in combination with letrozole versus placebo and letrozole in the neoadjuvant setting [13], the combination arm proved to be superior over letrozole and placebo with a higher significant response rate (68% vs. 59%) [13].…”
Section: Resultsmentioning
confidence: 99%
“…We demonstrated that nuclear ERα phosphorylated on serine 118 (pERα) is a strong marker of endocrine treatment response. This is an improving of the currently used IHC assessment for the ER expression, as it predict response to hormone therapy in only 36% to 55% of patients, with a small benefit with the progesterone receptor [11] marker evaluation. The molecules p44/42 MAPK and HIF-1, instead, was shown to be significantly associated with endocrine resistance [15].…”
Section: Can Mtor Inhibitors Really Prevent Endocrine Resistance?mentioning
confidence: 99%